ISOLATION OF ENDOPHYTIC BACTERIA ON GINSENG JAWA LEAVES (Talinum triangulare (Jacq.) Willd) - Nur, Istianti Irfa'a; Astuti, Winni; Kartika, Rudi (JURNAL ATOMIK, 2021)
Endophytic bacteria are bacteria that live in plant tissues. These bacteria produce extracellular enzymes, one of which is the lipase. This research was conducted to isolate the endophytic bacteria of Ginseng Jawa (Talinum triangulare (Jacq.) Willd) leaves which produced lipase and lipase screening from these bacteria. Isolation was carried out on nutrient agar (NA) media and screening of endophytic bacteria were carried out on nutrient agar (NA) media containing olive oil and Rhodamin B. Isolation results obtained by 5 single colonies and one colony of positive endophytic bacteria that produces lipase which characterized by the presence of orange-colored luminescence on the surface of the bacterial colony